BUILDING MAINTENANCE SYSTEMS OF PUBLIC HEALTH INSTITUTIONS IN GHANA: A CASE STUDY OF LA GENERAL HOSPITAL ACCRA - Zakari Mustapha; Justice Agbevade (Journal of Construction Project Management and Innovation)
It is highly desirable but hardly feasible to produce buildings that are maintenance free although much can be done at the design stage to reduce the amount of subsequent maintenance works. The research aim was to examine the various maintenance systems in use at La General Hospital in Accra. Field surveys and administration of questionnaires were used to collect the data. Most of the building structures in the institution have outlived their service period. Corrective maintenance was found to be in use and was ineffective in ensuring prompt remedial works. The level of manpower required (skilled) was also lacking. In view of these findings and by way of recommendations, it was suggested that management should adopt a maintenance policy for effective use in the institution and the entire scheme of corrective maintenance be re-structured. Furthermore, training, seminars and workshops should be organised for estate/maintenance officers to update their knowledge with regard to effective maintenance practices.